2011
DOI: 10.1158/1535-7163.mct-11-0401
|View full text |Cite
|
Sign up to set email alerts
|

The NEDD8-Activating Enzyme Inhibitor, MLN4924, Cooperates with TRAIL to Augment Apoptosis through Facilitating c-FLIP Degradation in Head and Neck Cancer Cells

Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is a tumor-selective cytokine with potential anticancer activity and is currently under clinical testing. Head and neck squamous cell carcinoma (HNSCC), like other cancer types, exhibits varied sensitivity to TRAIL. MLN4924 is a newly developed investigational small molecule inhibitor of NEDD8-activating enzyme with potent anticancer activity. This study reveals a novel function of MLN4924 in synergizing with TRAIL to induce apoptosis in HNSCC cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 35 publications
3
37
0
Order By: Relevance
“…Importantly, both the induction of rereplication and lack of apoptotic response in Cal27 or in FaDu cells treated with low pevonedistat concentrations (20-100 nmol/L) reported here is in contrast to the robust apoptosis observed in a previous study in SqCC/Y1 or in Tr146 HNSCC cells (55% and 65% of cells) treated with 5-to 10-fold higher doses of pevonedistat (0.5 and 1 mmol/L, respectively; ref. 67). This significant apoptotic response was attributed to the induction of c-FLIP degradation, which the authors showed to be independent of NEDD8 inhibition (67).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, both the induction of rereplication and lack of apoptotic response in Cal27 or in FaDu cells treated with low pevonedistat concentrations (20-100 nmol/L) reported here is in contrast to the robust apoptosis observed in a previous study in SqCC/Y1 or in Tr146 HNSCC cells (55% and 65% of cells) treated with 5-to 10-fold higher doses of pevonedistat (0.5 and 1 mmol/L, respectively; ref. 67). This significant apoptotic response was attributed to the induction of c-FLIP degradation, which the authors showed to be independent of NEDD8 inhibition (67).…”
Section: Discussionmentioning
confidence: 99%
“…67). This significant apoptotic response was attributed to the induction of c-FLIP degradation, which the authors showed to be independent of NEDD8 inhibition (67). Furthermore, it is now abundantly clear that hundereds of cellular proteins are regulated through neddylation, and consistently, pevonedistat inhibits several signal transduction pathways, including the NFkB, AKT, and the mTOR signaling pathways, in addition to cullin-signaling (28,29,(63)(64)(65)(66).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the tumourpromoting role of Smurf1, Smurf2 has been suggested to function as a tumour suppressor gene since ablation of Smurf2 in mice resulted in increased susceptibility to various types of cancers in aged mice 61 . We noted that the NAE inhibitor MLN4924 has been recently identified as a novel approach to the treatment of acute myeloid leukaemia, head and neck cancer and liver cancer [62][63][64] . In addition, MLN4924 was demonstrated to inhibit tumour growth in lung cancer xenografts 65 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies examined the role of JNK in mediating the apoptotic effect of several pharmacological agents or anticancer drugs in HNSCC cell lines, including N-(4-hydroxyphenyl) retinamide (4HPR), pepsin-digested bovine lactoferrin, 5-aminolevulinic acid, MLN4924, 6-(N, N -dimethylamino)-2-(naphthalene-1-yl) -4-quinazolinone, fomitoside-K, mevastatin and AZD8055 (an mTOR inhibitor), and their biological mechanisms of apoptosis (48)(49)(50)(51)(52)(53)(54)(55). Consistent with the present results, an antitumor role of JNK has been proposed upon treatment of HNSCC cells with the JNK inhibitor SP600125, which diminished the aforementioned pharmacological agents-induced apoptosis (47)(48)(49)(50)(51)(52)(53)(54). Similarly, Li and Johnson (56) demonstrated that pharmacological inhibition of JNK with SP600125 markedly inhibited bortezomib-induction of autophagy regulatory proteins and autophagosome formation in HNSCC.…”
Section: Discussionmentioning
confidence: 99%